Rational protein engineering of a ketoacids decarboxylase for efficient production of 1,2,4-butanetriol from arabinose - Xiaolin Shen; Hongchao Xu; Tong Wang; Ruihua Zhang; Xinxiao Sun; Qipeng Yuan; Jia Wang (Biotechnology for Biofuels and Bioproducts, 2023)
Abstract Background Lignocellulose, the most abundant non-edible feedstock on Earth, holds substantial potential for eco-friendly chemicals, fuels, and pharmaceuticals production. Glucose, xylose, and arabinose are primary components in lignocellulose, and their efficient conversion into high-value products is vital for economic viability. While glucose and xylose have been explored for such purpose, arabinose has been relatively overlooked. Results This study demonstrates a microbial platform for producing 1,2,4-butanetriol (BTO) from arabinose, a versatile compound with diverse applications in military, polymer, rubber and pharmaceutical industries. The screening of the key pathway enzyme, keto acids decarboxylase, facilitated the production of 276.7 mg/L of BTO from arabinose in Escherichia coli. Through protein engineering of the rate-limiting enzyme KivD, which involved reducing the size of the binding pocket to accommodate a smaller substrate, its activity improved threefold, resulting in an increase in the BTO titer to 475.1 mg/L. Additionally, modular optimization was employed to adjust the expression levels of pathway genes, further enhancing BTO production to 705.1 mg/L. Conclusion The present study showcases a promising microbial platform for sustainable BTO production from arabinose. These works widen the spectrum of potential lignocellulosic products and lays the foundation for comprehensive utilization of lignocellulosic components.